Effect of the turning characteristics of underfloor wheel lathes on the evolution of wheel polygonisation. (May 2019) - Cui, Dabin; An, Boyang; Allen, Paul; Wang, Ruichen; Wang, Ping; Wen, Zefeng; Li, Li
During both running and wheel cut operations, wheels of railway vehicles and the friction rollers that support and drive the wheelset on a typical wheel cut lathe are subject to wear and hence are likely to develop out-of-round characteristics after sustained use. The resulting out-of-round wheels can significantly affect the ride quality and can potentially increase the incidence of fatigue-related component failures due to the resulting higher intensity loading cycles. Furthermore, the corresponding out-of-round characteristics of the lathe's friction rollers will continue to degrade the subsequent cut quality of wheels. For the analysis of the out-of-round characteristics caused by an underfloor wheel lathe used for the high-speed trains in China, a mathematical model based on a typical electric multiple unit (EMU) vehicle's wheelsets and their interactions with the wheel lathe friction rollers was established. Factors influencing the cut quality of the wheels, including the number of cuts, eccentricity forms of the friction rollers and the longitudinal spacing of the two rollers, have been analysed. The results show that two cuts can effectively remove the higher order polygon on the wheel surface. The eccentricity and phase angle of the friction rollers have no influence on the cut quality of higher order polygons, whereas they are the primary cause for the fourth-order polygons. The severity of the fourth-order polygon depends on the level and the phase of the eccentricity of the friction rollers. The space of the two rollers can also significantly affect the cut quality. Obtaining the theoretical and practical value for the maintenance of polygonised wheels using the underfloor lathe is the main outcome of this study.